1996
DOI: 10.1093/oxfordjournals.humrep.a019092
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy: Prognostic models for the probability of achieving an ongoing pregnancy after in-vitro fertilization and the importance of testing their predictive value

Abstract: The aim of this study was to create reliable models to predict the probability of achieving an ongoing pregnancy during in-vitro fertilization (IVF) treatment: model A, at the start of the first treatment, model B at the time of embryo transfer, and model C, during the second treatment at the end of the first IVF treatment. Prognostic models were created using data from the University Hospital Nijmegen (n = 757) and applied to the data from the Catharina Hospital Eindhoven (n = 432), The Netherlands, to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…In the latter case, our model indicates that appropriate preventive strategies should be taken. In this context, it should be noted that prediction models often overestimate the predictive capacity when assessed in the same cohort in whom they have been developed [40,41]. Thus, an external validation of the present nomogram is needed to define its applicability in detecting patients at risk of developing moderate or severe OHSS.…”
Section: Discussionmentioning
confidence: 97%
“…In the latter case, our model indicates that appropriate preventive strategies should be taken. In this context, it should be noted that prediction models often overestimate the predictive capacity when assessed in the same cohort in whom they have been developed [40,41]. Thus, an external validation of the present nomogram is needed to define its applicability in detecting patients at risk of developing moderate or severe OHSS.…”
Section: Discussionmentioning
confidence: 97%
“…Stolwijk et al [29] developed a model of pregnancy after implantation and included the number and quality of the embryos in the model. They suggested that the probability of implantation was greatly increased in the presence of at least one good embryo and by higher numbers of embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors related to a higher cumulative pregnancy rate are duration of infertility less than 2 years, a previous pregnancy with the same partner and female age < 30 years. In these instances, couples could be encouraged to use less invasive treatments for up to 2-3 years because they have a similar chance of achieving pregnancy without treatment [32,33]. ART (IVF or ICSI) is indicated as first treatment option when the duration of UI is at least 3 years.…”
Section: How Many Iui Cycles Should Be Performed In Patients With Ui?mentioning
confidence: 99%